Venom biotechnology: casting light on nature’s deadliest weapons using synthetic biology - Lüddecke, Tim; Paas, Anne; Harris, Richard J.; Talmann, Lea; Kirchhoff, Kim N.; Billion, André; Hardes, Kornelia; Steinbrink, Antje; Gerlach, Doreen; Fry, Bryan G.; Vilcinskas, Andreas (Frontiers in Bioengineering and Biotechnology, 2023)
Venoms are complex chemical arsenals that have evolved independently many times in the animal kingdom. Venoms have attracted the interest of researchers because they are an important innovation that has contributed greatly to the evolutionary success of many animals, and their medical relevance offers significant potential for drug discovery. During the last decade, venom research has been revolutionized by the application of systems biology, giving rise to a novel field known as venomics. More recently, biotechnology has also made an increasing impact in this field. Its methods provide the means to disentangle and study venom systems across all levels of biological organization and, given their tremendous impact on the life sciences, these pivotal tools greatly facilitate the coherent understanding of venom system organization, development, biochemistry, and therapeutic activity. Even so, we lack a comprehensive overview of major advances achieved by applying biotechnology to venom systems. This review therefore considers the methods, insights, and potential future developments of biotechnological applications in the field of venom research. We follow the levels of biological organization and structure, starting with the methods used to study the genomic blueprint and genetic machinery of venoms, followed gene products and their functional phenotypes. We argue that biotechnology can answer some of the most urgent questions in venom research, particularly when multiple approaches are combined together, and with other venomics technologies.